Peran Tenaga Kesehatan dalam Menjamin Layanan Obstetri-Ginekologi di Tengah Krisis Bencana - Abub luthfi (STIKES Columbia Asia Medan, 2025)
Natural and non-natural disasters significantly disrupt healthcare systems, particularly obstetric and gynecological services, which are highly vulnerable to service interruptions and quality decline. Pregnant women, postpartum mothers, and newborns face an increased risk of complications and mortality without adequate medical care. Health professionals play a crucial role in ensuring the continuity of reproductive health services through the implementation of the Minimum Initial Service Package (MISP), emergency management, health education, and intersectoral coordination. However, challenges such as limited resources, psychological pressure, and lack of specialized training hinder optimal performance. Therefore, strengthening the capacity of healthcare workers, enhancing disaster preparedness, providing adequate logistics, and enacting supportive governmental policies are essential to maintain effective obstetric-gynecological care during crises. This literature review comprehensively discusses the role of health workers in ensuring reproductive health services in disaster settings as a strategy to improve access and service quality during emergencies.